Meningkatkan Penalaran Kritis Siswa Melalui Model Pbl Berbantuan Lkpd Materi Aku Berkembang Kelas Iv - Suwis Suwis; Andarweni Astuti (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2023)
The background of this research arises from the existence of problems in learning models that do not stimulate students to think critically, such as monotonous teaching methods. To overcome this, the Problem Based Learning (PBL) Learning Model is considered as a potential solution to improve students' critical reasoning abilities. This study aims to improve critical reasoning abilities and achieve student learning outcomes in Catholic Religious Education subjects. In achieving these objectives, this study used a descriptive approach through classroom action research methods with two cycles. The results of the first cycle can be seen from the student scores, there are 3 students who belong to the proficient category, 6 students in the proficient category, and 5 students in the decent category. Even so, the level of students' critical reasoning is not optimal, only reaching 72.5%. However, in the second cycle there was a significant increase with 11 students in the proficient category, 3 students in the proficient category, and 1 student in the feasible category. This indicates a significant improvement in students' understanding of learning material after implementing PBL with the help of Student Worksheets (LKPD). Students' critical thinking skills also increased, reaching 82%. The implications of these findings confirm that an approach that encourages active student participation through PBL with the support of LKPD has a positive impact on increasing critical reasoning abilities and student learning achievement.